Preparation and Analysis of Antimicrobial Activity of Fish Mucus Extract from Piaractus Brachypomus as a Natural Preservative for Fish - Charles, S.L.; E, M.H.; Kumar, T.S.; Чарльз, С.Л.; Е, М.Х.; Кумар, Т.С. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
The increasing demand for natural and sustainable alternatives to chemical preservatives has led to growing interest in bioactive compounds derived from aquatic organisms. Fish skin mucus, rich in antimicrobial proteins and peptides, presents a promising source for such applications. However, there is limited research on the efficacy of fish mucus extracts as natural preservatives for fish and meat products. This study explores the preservative potential of fish skin mucus from the red-bellied Pacu fish (Piaractus brachypomus). Aim. To prepare and evaluate the bioactive properties of fish skin mucus extract from Piaractus brachypomus for potential use as a natural preservative. Methods. Fish skin mucus was collected and processed using acid and aqueous extraction methods. Protein content was quantified using the Bradford assay, and protein profiles were analyzed via SDS-PAGE. Antibacterial activity of both extracts was tested against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus haemolyticus, Klebsiella sp., and Salmonella sp. at various concentrations (25 µL, 50 µL, 75 µL, and 100 µL). The acid extract was further evaluated for cytotoxicity, antioxidant activity, and efficacy as a preservative on fish fillets through a microbial load analysis over 5 hours at each hour. Results. The acid extract exhibited significant antibacterial activity, particularly at higher concentrations, while the aqueous extract showed negligible effects. Cytotoxicity assays indicated that the acid extract was non-toxic even at high concentrations (>70% cell viability). Although antioxidant activity was minimal, microbial load on treated fish fillets was reduced by approximately 40% compared to untreated controls. Conclusions. The acid extract of fish skin mucus from Piaractus brachypomus demonstrated strong antibacterial effects, low cytotoxicity, and high potential to reduce microbial contamination on fish meat during short-term exposure. These findings suggest that it may serve as a safe and effective natural preservative for improving fish quality and shelf life, particularly under typical market conditions, and long storage in refrigerator conditions.